Influence of organobentonite structure on toluene adsorption from water solution - Vidal, Nuria Carolina (2012)
Due to increase water pollution by organic compound derived from hydrocarbons such as toluene, several alternative technologies for remediation of polluted water have been originated. In this work natural bentonites were modified with cetyltrimethylammonium (CTMA+) for obtaining organophilic bentonites. The obtained CTMAbentonites would be suitable for use as adsorbents of toluene present in water. The influence of structural characteristics of CTMA-bentonites on their adsorption capacity was studied. It was shown that adsorption of toluene depended on homogeneous interlayer space associated with arrangements of CTMA+ paraffin-monolayer and bilayer models, accompanied by a high degree ordering of the carbon chain of organic cation in both arrangements. However, packing density would not have an evident influence on the retention capacity of these materials. The solids obtained were characterized by chemical analysis, X-ray diffractions and infrared spectroscopy. Toluene adsorption was measured by UV?visible spectrophotometer. Adsorption capacity was studied by determining adsorption isotherms and adsorption coefficient calculation. The adsorption isotherms were straight-line indicating a partition phenomenon of toluene between the aqueous and organic phase present in organophilic bentonites.